Medical revalidation as professional regulatory reform: challenging the power of enforceable trust in the United Kingdom - Spendlove, Zoey (Elsevier, 2018)
For more than two decades, international healthcare crises and ensuing political debates have led to increasing professional governance and regulatory policy reform. Governance and policy reforms, commonly representing a shift from embodied trust in professionals to state enforceable trust, have challenged professional power and self-regulatory privileges. However, controversy remains as to whether such policies do actually shift the balance of power and what the resulting effects of policy introduction would be. This paper explores the roll-out and operationalisation of revalidation as medical regulatory reform within a United Kingdom National Health Service hospital from 2012-2013, and its impact upon professional power. Revalidation policy was subject to the existing governance and management structures of the organisation, resulting in the formal policy process being shaped at the local level. This paper explores how the disorganised nature of the organisation hindered rather than facilitated robust processes of professional governance and regulation, fostering formalistic rather than genuine professional engagement with the policy process. Formalistic engagement seemingly assisted the medical profession in retaining self-regulatory privileges whilst maintaining professional power over the policy process. The paper concludes by challenging the concept of state enforceable trust and the theorisation that professional groups are effectively regulated and controlled by means of national and organisational objectives, such as revalidation.